“Beyond the Sayan Mountains”: Evolution of Ethnic and Territorial Identity of Natives of Tuva Who Migrated to Other Regions of Russia - Lysenko, Oleg V.; Shirap, Regina O. (The New Research of Tuva, 2025)
The article analyzes the issues of transformation of local and ethnic identity among Tuvans during their migration from Tuva to other regions of the country. The study is based on in-depth interviews with 11 informants, conducted online in 2025: Tuvans, natives of the republic, residing in other regions of Russia and abroad. The authors identify two main scenarios for migration: the rational choice in favor of obtaining an education at a prestigious university in the country, and spontaneous decisions related to the desire to escape routine life, see large cities, and loosen family ties. Gender aspects of migration are emphasized, wherein women seek to go beyond the traditional perception of their role in Tuvan society by obtaining education, achieving professional self-realization in large cities, and consciously choosing their priorities. Adaptation of Tuvan migrants is often accompanied by linguistic, cultural, and everyday challenges; however, ethnic affiliation serves as a resource for overcoming these issues through mutual assistance and the formation of community associations (“zemlyachestvo”). Emotional ties to the homeland remain strong, but many respondents do not plan to return for a number of reasons. The authors conclude that with increasing duration of residence outside their homeland, Tuvans experience a strengthening of ethnic identity alongside a simultaneous weakening of territorial identity.